2003
DOI: 10.1046/j.1523-1747.2003.12304.x
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Overexpression of Human Telomerase Reverse Transcriptase but Not c-myc Blocks Terminal Differentiation In Human HaCaT Skin Keratinocytes

Abstract: Formation of a well structured epidermis strictly depends on a tight balance between proliferation and differentiation. Accordingly, telomerase, which is restricted to proliferating cells, is downregulated with differentiation. It is unclear, however, whether this inhibition is essential to or only a consequence of the differentiation process. By studying different variants of the HaCaT skin keratinocytes we now show that constitutive overexpression of human telomerase reverse transcriptase (hTERT) in HaCaT-TE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 52 publications
2
38
0
Order By: Relevance
“…Sections of 1-, 2-and 4-week-old cultures were stained with antibodies against the basement membrane component type IV collagen (coll IV) as well as characteristic early (keratin K1/10 and involucrin) and late (filaggrin and loricrin) epidermal differentiation markers. As demonstrated in Figure 7 for 4-week-old cultures, Hneo control cells exhibited a similar distribution of differentiation markers as described previously for the parental HaCaT cells (Cerezo et al, 2003). Keratin 1 and 10 were expressed in all suprabasal layers (Figure 7a), the honeycomb-like involucrin staining started in the second suprabasal layer (Figure 7b) and filaggrin was present in the uppermost living cell layer (Figure 7c).…”
Section: Differentiation Is Impaired In Cyclin D1-overexpressing Cellssupporting
confidence: 78%
See 2 more Smart Citations
“…Sections of 1-, 2-and 4-week-old cultures were stained with antibodies against the basement membrane component type IV collagen (coll IV) as well as characteristic early (keratin K1/10 and involucrin) and late (filaggrin and loricrin) epidermal differentiation markers. As demonstrated in Figure 7 for 4-week-old cultures, Hneo control cells exhibited a similar distribution of differentiation markers as described previously for the parental HaCaT cells (Cerezo et al, 2003). Keratin 1 and 10 were expressed in all suprabasal layers (Figure 7a), the honeycomb-like involucrin staining started in the second suprabasal layer (Figure 7b) and filaggrin was present in the uppermost living cell layer (Figure 7c).…”
Section: Differentiation Is Impaired In Cyclin D1-overexpressing Cellssupporting
confidence: 78%
“…HaCaT cells are particularly suited because they exhibit a number of chromosomal aberrations characteristic for skin SCCs but lack gain of 11q, are non-tumorigenic, and still possess the ability to form a normally differentiated epidermis-like epithelium under appropriate conditions (Boukamp et al, 1988(Boukamp et al, , 1997Lehman et al, 1993;Schoop et al, 1999;Cerezo et al, 2003). Figure 2 Cyclin D1 is overexpressed in keratoacanthomas (KAs) and squamous cell carcinomas (SCCs).…”
Section: Functional Consequences Of Cyclin D1 Overexpressionmentioning
confidence: 99%
See 1 more Smart Citation
“…75,76 As stem and progenitor cells become more differentiated-or when tumor cells are induced to differentiate, the activity of this enzyme sharply decreases. 71,77,78 In essence, telomerase activity is an inverse marker of differentiation. Consistent with this telomerase phenomenon, the induction of differentiation in the H6c7 pancreatic cells with the adenylate cyclase stimulator, forskolin and IBMX, induced a sharp decline in telomerase activity.…”
Section: Discussionmentioning
confidence: 99%
“…hTERT-expressing cells show extensive changes in gene expression patterns (Smith et al, 2003;Cerezo et al, 2003). The ability of hTERT to exert a variety of effects that counteract cell death is striking (Sung et al, 2005) and these effects have been reported also in whole animals overexpressing TERT; in mice this protects against experimental heart failure ( Oh et al, 2001) and has many other effects in the cardiovascular system (Serrano and Andres, 2004).…”
Section: Approaches To Improved Cell Transplantation Using Genomicsmentioning
confidence: 99%